'More open borders and deep structural transformation'. Issue 4 (7th June 2021) - Tebble, Adam James
ABSTRACT: Building upon recent work on epistemic varieties of liberalism, avant-garde political agency and the theory and practice of activism, I claim that a liberal defence of more open borders does not presuppose either indifference to the problem of the deep structural sources of poverty in poorer countries, or the absence of an account of those structures' transformation. Rather, it is claimed that in addition to the remittance of money and other economic goods to alleviate the symptoms of poverty, more open borders facilitate the remittance of norms and values in terms of which individuals and activist communities in poorer countries may transform the deep structures and institutions that are poverty's sources. This liberal account of more open borders and deep structural transformation also makes possible the non-coercive discharge of obligations of global justice on the part of wealthier states to the world's poor, when poorer nations are either unable or unwilling to discharge them themselves.